2016
DOI: 10.1155/2016/5694251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Air Quality Model Performance for Simulating Long-Range Transport and Local Pollution of PM2.5in Japan

Abstract: The Community Multiscale Air Quality Model (CMAQ) v5.0.2 was applied to PM2.5simulation in Japan, which is strongly affected by long-range transport (LRT) from anthropogenic sources in the Asian Continent, for one year from April 2010 to March 2011. The model performance for LRT and local pollution (LP) of PM2.5was evaluated to identify the model processes that need to be improved. CMAQ well simulated temporal and spatial variation patterns of PM2.5but underestimated the concentration level by 15% on average. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…WRF configurations are almost same as Shimadera [2], in which the simulated meteorological fields in 2010 well captured the observations. CMAQ configurations are almost same as Shimadera [3] except for emissions from power plants, in which the simulated pollutant concentrations in 2010 well captured the observations. Three simulations were carried out against varying emissions from power generation; use of the emissions in 2010 (2010case); use of the emissions in 2012 (2012case) and not considering the emissions from power generation (base).…”
Section: Outline Of Modelmentioning
confidence: 59%
“…WRF configurations are almost same as Shimadera [2], in which the simulated meteorological fields in 2010 well captured the observations. CMAQ configurations are almost same as Shimadera [3] except for emissions from power plants, in which the simulated pollutant concentrations in 2010 well captured the observations. Three simulations were carried out against varying emissions from power generation; use of the emissions in 2010 (2010case); use of the emissions in 2012 (2012case) and not considering the emissions from power generation (base).…”
Section: Outline Of Modelmentioning
confidence: 59%
“…Aikawa et al (2010) observed negative correlation between longitude and particulate sulfate in Japan, which is one of the constituents of PM 2.5 , and reproduced this longitudinal gradient by chemical transport model. Shimadera et al (2016) also showed the longitudinal gradient both in the observed and simulated concentrations of PM 2.5 . In both studies, the influence of long range transport from the Asian continent was suggested.…”
Section: Data Setmentioning
confidence: 71%
“…An accurate estimate of spatial distribution of air pollutants is the essential piece of information to evaluate the risks to human health and/or the air quality policy quantitatively. To obtain the distribution, the chemical transport model (CTM) has been extensively used in the field of air quality study (e.g., Emmons et al, 2010;Chatani et al, 2014;Shimadera et al, 2016). CTM simulates physical and chemical processes including emission, advection, transformation and depositions, and reproduces the temporal and spatial variation of air pollutant concentrations by complicated and demanding computation.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical domain consisted of 30 layers with the middle heights of the first, second, and third layers being 28 m, 92 m, and 190 m, respectively. The physics parameterizations and input data for WRF and the chemical mechanisms, including the Carbon Bond mechanism developed in 2005 (CB05) [36], the next generation model of CBM-IV, for CMAQ were the same as those used by Shimadera et al [37]. Emission data for CMAQ were produced from the same datasets as those used by Uranishi et al [38], including the Japan Auto-Oil Program Emission Inventory-Data Base for vehicles (JEI-DB) in the year 2010 developed by the Japan Petroleum Energy Center [39].…”
Section: Simulation Setupmentioning
confidence: 99%